2004
DOI: 10.1002/srin.200405782
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of Selenium Impurities During the Addition of Se‐Containing Manganese to Steel Melt

Abstract: Manganese is an important alloy addition for alloy steels. It is normally added to steel melts as ferromanganese. However, for the adjustment of melt composition, manganese metal is used as a trimming addition since it has lower levels of impurities than ferromanganese. The manganese used for this purpose is obtained from the electrolytic processing route wherein selenium-containing additives are added to the electrolyte bath to improve the current efficiency. This practice introduces selenium to the manganese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The hot ductility curve of stainless steel 1.4301 (18%Cr-8.7%Ni) tested using a constant cooling rate of 3 K/s from the melting to the test temperature and the same strain rate [13] is also shown for comparison. The ZDT and ZST of the steel 1.4301 are about MnS and MnSe [14] are stable compounds. MnS and MnSe form unlimited solutions in the solid and liquid states in the MnS-MnSe phase diagram [16].…”
Section: K/smentioning
confidence: 96%
See 1 more Smart Citation
“…The hot ductility curve of stainless steel 1.4301 (18%Cr-8.7%Ni) tested using a constant cooling rate of 3 K/s from the melting to the test temperature and the same strain rate [13] is also shown for comparison. The ZDT and ZST of the steel 1.4301 are about MnS and MnSe [14] are stable compounds. MnS and MnSe form unlimited solutions in the solid and liquid states in the MnS-MnSe phase diagram [16].…”
Section: K/smentioning
confidence: 96%
“…Selenium in the steel could come from the Mn metal used as manganese source. It has been reported that selenium-containing additives are commonly added to the electrolyte as seleneous acid in order to improve the production efficiency of the electrolytic manganese metal [14]. The manganese produced in this process can become significantly contaminated with Se (e.g.…”
Section: K/smentioning
confidence: 99%
“…Selenium originates from the aqueous winning electrolysis and largely evaporates during alloying of steel melts thus causing potential environmental and working place hazards in elemental or compound form. [2] Hydrogen, also resulting from the aqueous electrolysis, is a critical impurity, which many high manganese steel grades are sensitive to. Its content is lowered by effusion annealing of EMM.…”
Section: Conventional Mn-bearing Alloying Agents For Steelmakingmentioning
confidence: 99%
“…Electrolytic manganese metal (“EMM”) features the highest chemical purity, apart from selenium and hydrogen in some EMM grades. Selenium originates from the aqueous winning electrolysis and largely evaporates during alloying of steel melts thus causing potential environmental and working place hazards in elemental or compound form . Hydrogen, also resulting from the aqueous electrolysis, is a critical impurity, which many high manganese steel grades are sensitive to.…”
Section: Introductionmentioning
confidence: 99%
“…Selenium can be introduced into the melts in the steel processing route, normally as impurity in the manganese metal. 9) About some positive effects of the selenium on the texture formation and the magnetic properties of the nonoriented electrical steels have already been reported. It is likely that the growth of the grains with soft magnetic orientations near the plane (001) is to be enhanced.…”
Section: (4)mentioning
confidence: 99%